Os efeitos da pandemia COVID-19 na educação de estudantes do ensino médio em condição de pobreza e vulnerabilidade social: o caso de uma escola particular do município de Vila Velha/ES - Mendes, Letícia Maria Borlini (2023)
This research delves into the challenges faced by education due to the COVID-19 pandemic, caused by the novel coronavirus (Sars-CoV-2), with a focus on the effects on high school students enrolled in Terra Vermelha School, a privately managed, nonprofit institution located in an area historically characterized by poverty and social vulnerability—the Greater Terra Vermelha, in the municipality of Vila Velha, Espírito Santo (ES). The discussions revolved around authors who address and problematize the central categories outlined for this work: poverty and social vulnerability and their relation to education (Arroyo, 2014; Carneiro, 2005; Codes, 2008; Nascimento, 2013; Cararo, 2015), youth (Dayrell, 2003; Sposito, Carrano, 2003; Dayrell, Carrano, 2014; Groppo, 2016), and high school (Krawczyk, 2011; Silva, 2015; Ferreira, 2017). The categories were debated based on the understanding of poverty as a multidimensional and complex phenomenon, a product of the capitalist mode of production and reproduction, and the challenges posed to education in the face of the paradox between being a means of overcoming poverty and being a reproducer of the established social order (Cararo, 2015). It incorporates youth into this context, problematizing different theoretical, analytical, and conceptual approaches, reinforcing, however, the youth as social subjects or rights holders, immersed in a life cycle driven by age-specific transformations and differentiated by social, cultural, economic, and political experiences that shape them in their numerous youthhoods (Dayrell, 2003). The study portrays historical tensions around high school, integrating youth and the issues specific to them in this scenario. To comprehend the effects of the COVID-19 pandemic on the education of high school students in conditions of poverty and social vulnerability, a single case study methodology was adopted, with Terra Vermelha School as the unit of analysis and the COVID-19 pandemic as the event. Eight high school students from the 3rd grade in the year 2022, three families of these students, and two managers from Terra Vermelha School participated in the research, with in-depth interviews conducted using a semi-structured study guide. Through the collaboration of the participants, it was concluded that the effects were, as a cause or consequence, of social, economic, and educational nature, and many of them were particularly felt by impoverished students and youth, whose living and survival conditions are more challenging. The deepening of poverty and educational inequality is highlighted, as well as the experience of a new routine imposed by remote classes, the structural vulnerabilities of homes, the effects on the work of family members, and consequently, income. Regarding high school, effects were perceived in learning, socialization, and the future plans of each youth, widening the gap between what this stage of basic education provides and what the youth expected from it.